Evaluation of Failure Capacity of Offshore Riser Protectors Under Vessel Impact - Syed, Z.I. (Springer New York LLC, 2018)
Conventional riser protectors, also known as riser-guards, are installed on fixed offshore platforms to protect risers from vessel impact. These space frame structures made of hollow mild steel tubular sections are mainly designed using the approach of boat fenders which may result in over- or under-protection provided to risers. Lack of in-depth study on the dynamic behavior and capacity of conventional riser-guards is considered to be the primary challenge for creative and efficient design of conventional riser protectors. This paper presents a detailed numerical investigation on the dynamic response, damage and failure mechanics of conventional steel riser-guards during accidental vessel collision using nonlinear finite element analysis. Collision forces equivalent to vessel collision with riser-guards for different spans were estimated to provide information for load-based design. Variation in damage patterns for broadside and bow impacts is presented for riser protectors with different spans. The actual capacity of a typical riser-guard in terms of maximum impact energy sustainable prior to failure was also determined from dynamic pushover analysis. The structural response and damage parameters presented in this study can be used for better understanding of damage mechanism and failure capacity of riser protectors which can act as a baseline for further design optimization, as well as the development of other alternative riser protection systems. Â© 2018 ASM International